ECONOMIC IMPACTS OF LANGUAGE PRESERVATION THROUGH PRIMARY SCHOOL EDUCATION - Sultanova Shohistaxon Shavkatovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation: This article explores the economic implications of preserving minority and indigenous languages through primary school education. It examines how integrating mother-tongue instruction into early education not only supports linguistic and cultural heritage but also contributes to human capital development, labor market competitiveness, and long-term economic growth. Drawing on global case studies, the paper highlights how language preservation policies can reduce educational inequality, increase literacy rates, and promote social cohesion, ultimately translating into measurable economic benefits for communities and nations.